Classification errors of navigation measurements - Харченко, В.П.; Міхалочкін, М.А.; Махди, Касем Аббуд (Proceedings of National Aviation University (archive), 2009)
Radio navigation facilities and systems inaccuracy sources, their classification and description as well as most spread amount characteristics and assessments have been analyzed.